2020
DOI: 10.1101/2020.06.05.20121566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 on clinical practice, income, health and lifestyle behavior of Brazilian urologists

Abstract: Objectives: To evaluate the impact of COVID-19 on clinical practice, income, health and lifestyle behavior of Brazilian urologists during the month of April 2020. Materials and Methods: A 39-question, web-based survey was sent to all urologist members of the Brazilian Society of Urology. We assessed socio-demographic, professional, health and behavior parameters. The primary goal was to evaluate changes in urologists ′ clinical practice and income after two months of COVID-19. We also looked at geographical d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
2
21
1
Order By: Relevance
“…These results reveal the severity and significance of the implemented changes for urologists. Similar results were obtained in other surveys conducted worldwide [ 6 , 7 , 8 ]. For example, in Germany, 97% of urologists indicated that their routine work was moderately to very strongly impacted by the COVID-19 pandemic, with only 0.3% believing that the outbreak did not affect their work [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results reveal the severity and significance of the implemented changes for urologists. Similar results were obtained in other surveys conducted worldwide [ 6 , 7 , 8 ]. For example, in Germany, 97% of urologists indicated that their routine work was moderately to very strongly impacted by the COVID-19 pandemic, with only 0.3% believing that the outbreak did not affect their work [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, despite initial success with flattening the COVID-19 incidence curve, escalating restrictions, further health care restructuration (including the opening of COVID-19-dedicated hospitals), and unexplored COVID-19 fear likely led to indirect adverse effects of the pandemic also impacting Polish physicians and their work. Therefore, COVID-19, a droplets-transmitted respiratory infection, despite not being in the initial scope of treatment of urologists, has impacted all areas of urology including emergencies, outpatient clinics, elective surgeries, as well as physicians’ everyday lives [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 19 articles included in this scoping review [2][3][4][5][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], four explored changes in all three domains, namely weight, diet and exercise [2,4,5,24], three explored changes in both weight and diet and weight and exercise, three explored changes in both diet and exercise [22][23][24], and the rest explored each domain exclusively (Table 2, Figure 1). A summary of the impact of COVID-19 on the overall change in perceived weight status, dietary behaviors, physical activity behaviors, sedentary behaviors and other lifestyle behaviors are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Social distancing has been introduced more than four months ago and is plainly effective throughout the country, with no signs that it will be relaxed in the next weeks. A recent study showed a dramatic reduction in elective patient visits and surgical procedures in the whole country (4). Given the continental dimensions and signifi cant geographical and socioeconomic heterogeneity of the country, the pandemic impact has also been heterogeneous across different regions in Brazil (5).…”
Section: Expert Opinionmentioning
confidence: 99%